2003
DOI: 10.1063/1.1568077
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure, binding energy, and magnetic properties of iron atoms supported on a polyaromatic hydrocarbon

Abstract: The atomic structure, energetics, and properties of gas-phase cluster complexes containing coronene (C 24 H 12) molecule and up to two iron atoms are studied for the first time using density functional theory and generalized gradient approximation for exchange and correlation. The geometries of the neutral and cationic iron-coronene complexes are optimized without symmetry constraint and by examining the possibility that iron atoms could occupy various sites via individual or bridging interactions. In both neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 22 publications
9
37
8
Order By: Relevance
“…In addition, this study has also allowed us to assess the similarities and differences between Co m ͑coronene͒ and the previously reported 16 ground state geometries of Fe m ͑coronene͒ complexes. Motivated both by this imbalance and the absence of any studies combining both experimental and theoretical efforts on these complexes, we have initiated a systematic experimental and theoretical study on Co m ͑coronene͒ ͑m =1-2͒ complexes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, this study has also allowed us to assess the similarities and differences between Co m ͑coronene͒ and the previously reported 16 ground state geometries of Fe m ͑coronene͒ complexes. Motivated both by this imbalance and the absence of any studies combining both experimental and theoretical efforts on these complexes, we have initiated a systematic experimental and theoretical study on Co m ͑coronene͒ ͑m =1-2͒ complexes.…”
Section: Introductionmentioning
confidence: 92%
“…15,16 In one of the earliest gas-phase experimental studies 11 on metal-coronene complexes, Dunbar and co-workers studied the interaction of metal cations such as Mg + , Al + , Si + , In + , Pb + , and Bi + with coronene molecules. However, a complementary theoretical study 16 on Fe m ͑coronene͒ ͑m =1,2͒ complexes provided a different view of the structures. It was reported that the TM-coronene cationic complexes reacted readily and formed TM͑coronene͒ 2 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For transition metal atoms, this can be more than just simple electrostatic attraction; in such complexes, the occupied metal d orbitals can donate charge to the PAH unfilled à orbitals, and the occupied PAH orbitals can donate charge into empty or partly occupied metal orbitals to produce a strong, pseudocovalent bond. These compounds have begun to attract increasing interest in recent years in fields such as physical and organometallic chemistry for their interesting and unique bonding characteristics (see, e.g., Buchanan et al 1998;Senapati et al 2003). Given the relative cosmic abundance of the metals iron and magnesium, complexes involving these metals or their ions might well be important in the astrophysical context (Serra et al 1992;Klotz et al 1995).…”
Section: The Effect Of Metal Complexation On the Spectrummentioning
confidence: 98%
“…We use this molecular system as a prototype for a graphene sheet, where on the hollow site of the central ring, a cobalt atom is introduced as a local defect. Metal-coronene complexes are currently of experimental [61][62][63][64] and theoretical [65,66] interest, because the delocalised π electrons in coronene make it a suitable model system for studying the interaction of metals with extended systems. These papers show that many different metals (TMs and otherwise) can form bound ionic and neutral complexes with coronene.…”
Section: Cobalt On Coronenementioning
confidence: 99%